A Report of 61 Cases of Retroperitoneal Laparoscopic Nephron-Sparing Surgery and Factors Affecting Postoperative Renal Function. (16th October 2021) - Song, Yao; Pang, Songqiang; Yang, Jinqiang; Li, Sen; He, Yaqiang; Luo, Gongtang
Abstract : Objective . To explore the situation of 61 patients with renal tumors who underwent retroperitoneal laparoscopic nephron-sparing surgery (RLNSS) and the factors affecting postoperative renal function. Methods . A total of 61 patients with renal tumors who underwent RLNSS in our hospital from January 2018 to January 2021 were included in this study. All patients were treated with RLNSS. The clinical data of patients were recorded. Before operation and 3 months after operation, the change value of glomerular filtration rate (ΔGFR) was measured by the Gates method. Multivariate linear regression was used to analyze the related factors affecting postoperative renal function. Results . All 61 patients successfully completed the operation. The mean operative time was 60–150 min‚ average (98.75 ± 14.38) min. The estimated intraoperative blood loss was 20–310 ml‚ average (107.93 ± 68.55) ml. Intraoperative warm ischemia time (WIT) was 0–39 min, with an average of (21.16 ± 6.47) min. All patients' pathological margins were negative after operation. In all patients, there were 5 postoperative complications, including 2 cases of renal wound bleeding (3.28%), 1 case of hematuria (1.64%), 1 case of urinary fistula (1.64%), and 1 case of subcutaneous emphysema (1.64%). There were significant differences in tumor diameter, preoperative GFR, operation time and WIT (P < 0.05 ). Multivariate analysis showed that tumor diameter, preoperative GFR, and WIT were all factors affecting the postoperative renal function of patients with RLNSS (P < 0.05 ). Conclusion . RLNSS has a good curative effect on patients with renal tumor, and tumor diameter, preoperative GFR, and WIT were all factors affecting the postoperative renal function of patients with RLNSS.